Variasi Konsentrasi Fase Gerak pada Analisis Hidrokuinon dalam Sabun Pemutih dengan Metode Kromatografi Kertas - Anik Eko Novitasari; Lailatul Fitriyah; Rosidah Rosidah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Hydroquinone is a compound that is often used in skin whitening beauty products. According to BPOM 2007, the use of hydroquinone at levels above 2% can cause skin disorders, namely hyperpigmentation which can lead to skin cancer. This research was conducted to qualitatively analyze the hydroquinone compound found in skin whitening soap which does not have a BPOM number. The aim of this research is to determine the presence of hydroquinone compounds contained in skin whitening soap samples and to determine the differences in Rf values ​​resulting from the comparison of the concentrations of the mobile phase used. Qualitative analysis was carried out by calculating the Rf value of paper chromatography using a comparison of variations in mobile phase concentration, namely 50% ethanol: chloroform (1: 1) and 90% ethanol: chloroform (1: 1). The analysis results show that the standard Rf value of hydroquinone from the eluent of 50% ethanol and chloroform is 0.46, where this Rf value is the same as the Rf value from sample number 5, namely 0.46. Meanwhile, the Rf value using 90% ethanol and chloroform eluents in sample No. 5 is 0.67, which is not the same as the standard Rf value, namely 0.56. Of the whitening soap samples, 1 sample showed a positive result containing hydroquinone.